Evaluation of the effects of pulsed wave LLLT on tibial diaphysis in two rat models of experimental osteoporosis, as examined by stereological and real-time PCR gene expression analyses. Issue 4 (May 2016) - Mohsenifar, Zhaleh; Fridoni, Mohammadjavad; Ghatrehsamani, Mahdi; Abdollahifar, Mohammad-amin; Abbaszadeh, Hojjatallah; Mostafavinia, Atarodalsadat; Fallahnezhad, Somaye; Asghari, Mohammadali; Bayat, Saba; Bayat, Mohammad
Abstract Osteoporosis (OP) and osteoporotic fracture are major public health issues for society; the burden for the affected individual is also high. Previous studies have shown that pulsed wave low-level laser therapy (PW LLLT) has osteogenic effects. This study intended to evaluate the impacts of PW LLLT on the cortical bone of osteoporotic rats' tibias in two experimental models, ovariectomized and dexamethasone-treated. We divided the rats into four ovariectomized induced OP (OVX-d) and four dexamethasone-treated (glucocorticoid-induced OP, GIOP) groups. A healthy (H) group of rats was considered for baseline evaluations. At 14 weeks following ovariectomy, we subdivided the OVX-d rats into the following groups: (i) control which had OP, (ii) OVX-d rats treated with alendronate (1 mg/kg), (iii) OVX-d rats treated with LLLT, and (iv) OVX-d rats treated with alendronate and PW LLLT. The remaining rats received dexamethasone over a 5-week period and were also subdivided into four groups: (i) control rats treated with intramuscular (i.m.) injections of distilled water (vehicle), (ii) rats treated with subcutaneous alendronate injections (1 mg/kg), (iii) laser-treated rats, and (iv) rats simultaneously treated with laser and alendronate. The rats received alendronate for 30 days and underwent PW LLLT (890 nm, 80 Hz, 0.972 J/cm2 ) three times per week during 8 weeks. Then, the right tibias were extracted and underwent a stereological analysis of histological parameters and real-time polymerase chain reaction (RT-PCR). A significant increase in cortical bone volume (mm3 ) existed in all study groups compared to the healthy rats. There were significant decreases in trabecular bone volume (mm3 ) in all study groups compared to the group of healthy rats. The control rats with OP and rats from the vehicle group showed significantly increased osteoclast numbers compared to most other groups. Alendronate significantly decreased osteoclast numbers in osteoporotic rats. Concurrent treatments (compounded by PW LLLT and alendronate) produce the same effect on osteoporotic bone.